Agricultural production system in arid and semi-arid regions - Begizew Golla (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
The arid and semi-arid regions comprise more than forty present of the Earth's land surface on which a large number of people situated and largely engaged in agriculture to meet their basic needs. However, agriculture in these regions are highly influenced by several factors including water limitation, extreme heat, frequent drought, bared and marginal soil, vulnerable topography for natural hazards, erosive rain and wind. In order to cope with these challenges a number of essential scientific investigation and cultural practices have continuously released, modified and recommended to sustain agriculture production in these regions. Some of these indispensable investigation and practice included that soil and water conservation, rain water harvesting and supplementary irrigation, use of stress tolerant crops and integrating of diverse farming system. So in this review it is attempted to discuss several points concerning arid and semi-arid land agricultural constraints and management action carried out to solve such constraints.